Proton probe measurement of fast advection of magnetic fields by hot electrons - Willingale, L; Thomas, A; Nilson, P; Kaluza, M; Bandyopadhyay, S; Dangor, A; Evans, R; Fernandes, P; Haines, MG; Kamperidis, C; Kingham, R; Minardi, S; et al. (2011)
A laser generated proton beam was used to measure the megagauss strength self-generated magnetic fields from a nanosecond laser interaction with an aluminum target. At intensities of 10 15 W cm -2, the significant hot electron production and strong heat fluxes result in non-local transport becoming important to describe the magnetic field dynamics. Two-dimensional implicit Vlasov-Fokker-Planck modeling shows that fast advection of the magnetic field from the focal region occurs via the Nernst effect at significantly higher velocities than the sound speed, v N/c s ≈ 10. © 2011 IOP Publishing Ltd.